Analysis of China’s FinTech Regulatory Sandbox: Development History and Future Prospects - Lei, Nuo (International Journal of Global Economics and Management, 2024)
This article provides an in-depth discussion of the impact of the development of financial technology (FinTech) on the digital transformation of commercial banks, the regulatory challenges they face, and the practice of regulatory innovation. By comprehensively analyzing relevant literature, the article reveals the positive role of FinTech in promoting financial service innovation, improving the efficiency of the financial system, and satisfying consumer demand. At the same time, it points out the new types of risks and challenges brought by the rapid development of FinTech, especially in the areas of regulatory adaptability, data security, and consumer protection. In addition, the paper discusses the application of regulatory sandboxes as a regulatory innovation tool in achieving a balance between fintech innovation and risk management and emphasizes the importance of cooperation between regulators, financial institutions, and technology companies. The healthy development of FinTech in the future requires a closer dialogue and cooperation between technology innovation and regulatory innovation, while international coordination on regulatory frameworks and standards is also crucial. This study aims to provide insights for researchers and practitioners in the field of FinTech and help FinTech continue to develop in a safe and orderly environment.